Assessing Farmers’ Household Food Insecurity Access Prevalence and Food Security Status in Southwest Nigeria - Falola (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2021)
A household is considered to be food secure when its occupants do not live-in hunger or fear of starvation. Prevalence of food insecurity is a major concern in Southwest Nigeria, most farm households live below the international standard. This study, therefore, assessed the household food security status of farmers in Southwest Nigeria. Primary data were obtained from 800 registered farmers selected through multi-stage sampling process in Ogun and Oyo States of Southwest Nigeria. Survey data were obtained with the use of Household Food Insecurity Access Scale (HFIAS) questionnaire. Data were analyzed using descriptive statistics and Factor analysis. Two main factors were retained with 65.9% of the total variance explained. The mean food insecurity score was 2.03±SD 0.95. Overall food security of 33.6% and 66.4% of food insecurity was recorded. Conclusively, the HFIAS measurement portrays assessment of farmers' household in Southwest Nigeria as food insecure due to low income from production. Hence, the need to formulate effective food security programmes, new farming techniques and methods to increase production to reduce food insecurity are vital remedies.